2005
DOI: 10.1016/j.jsgi.2004.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Placental Dysfunction in Suramin-Treated Rats: Impact of Maternal Diabetes and Effects of Antioxidative Treatment

Abstract: Suramin injections to pregnant rats cause a state of placental insufficiency, which in U rats resembles human preeclampsia. The induction of this condition is at least partly mediated by oxidative stress, and antagonized by antioxidative treatment. Maternal diabetes involves increased oxidative stress, and causes both maternal and fetal morbidity, which are only marginally affected by additional Suramin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…This presumption finds support in the similarity of placental data obtained in suramin-treated and FRD dams. Indeed, it has been showed that suramin treatment in dams drastically reduced placental and renal blood vessel areas, being these parameters indicative for the hypertensive state developed by these dams [34]. Interestingly, and in accordance with its improving effect on glucose homeostasis, metformin treatment in FRD dams fully prevented placental dysfunction.…”
Section: Discussionmentioning
confidence: 88%
“…This presumption finds support in the similarity of placental data obtained in suramin-treated and FRD dams. Indeed, it has been showed that suramin treatment in dams drastically reduced placental and renal blood vessel areas, being these parameters indicative for the hypertensive state developed by these dams [34]. Interestingly, and in accordance with its improving effect on glucose homeostasis, metformin treatment in FRD dams fully prevented placental dysfunction.…”
Section: Discussionmentioning
confidence: 88%
“…Estimations of 8-iso-PGF2␣ in fetal liver and maternal serum were performed largely in accordance with the instructions from the manufacturer (Cayman Chemical, Ann Arbor, MI), as described in previous work (31,50). The protein content of the liver samples was estimated by the method of Lowry et al (26), using bovine serum albumin as standard.…”
Section: ϫ⌬(Cp)mentioning
confidence: 99%
“…Such factors of the maternal environment include nutrient restriction (Woodall et al, 1996;Rudge et al, 1999;Redmer et al, 2004;Wu et al, 2006), oxidative stress (Maranghi et al, 1998;Nash et al, 2005;Myatt, 2006;Burdon et al, 2007), anemia (Crowe et al, 1995), hypoxia (Robinson et al, 1979(Robinson et al, , 1985Owens et al, 1987aOwens et al, , 2007Lynch and Bruce, 1989;Myatt, 2006), and hypoglycemia (Robinson et al, 1979;Lueder et al, 1992;Carver and Hay, 1995;Owens et al, 1987bOwens et al, , 2007. Nutrient restriction affects the development of the blastocyst, its implantation, and the subsequent development of the placenta (Cross and Mickelson, 2006).…”
Section: Discussionmentioning
confidence: 99%